Study Law Plunder Asset Without Sentencing as Alternative Giver Justice for States and Actors Act Criminal Corruption (Discourse Journal on Law and Society, 2025)
Regulated asset confiscation​ in criminal acts of corruption based on Article 18 paragraph (1) of Law Number 20 of 2001 concerning the Eradication of Corruption Crimes. A form of asset confiscation without punishment as an alternative to giving justice for the state and perpetrators of criminal acts of corruption consists of an asset confiscation system using the Non Conviction Based Asset Forfeiture model and implementing the mandate of UNCAC as the State. The establishment of legal rules regarding confiscation of assets without punishment as an alternative to providing justice for the state and perpetrators of criminal acts of corruption in realizing a welfare state, at least taken in several progressive legal steps, namely improving statutory regulations, strengthening coordination between law enforcement agencies, and speed up the completion of the Asset Return Law.